Exacerbation of headache during dihydroergotamine for chronic migraine does not alter outcome. (1st March 2016) - Eller, Michael; Gelfand, Amy A.; Riggins, Nina Y.; Shiboski, Stephen; Schankin, Christoph; Goadsby, Peter J.
Abstract : Objective: To evaluate whether headache exacerbation associated with IV dihydroergotamine (DHE) infusion predicts medium-term headache outcome in patients with chronic migraine. Methods: This was a retrospective chart review study of the UCSF Headache Center's use of IV DHE for chronic migraine from 2008 to 2012. Medium-term headache outcome was assessed at 6-week follow-up. Univariate and multivariate logistic regression models were used to assess for predictors of outcome. Results: Patients with chronic migraine (n = 274) were treated with a course of IV DHE. Of 214 with 6-week follow-up, 78% had medium-term headache benefit. In a univariate logistic regression model, headache exacerbation with DHE was associated with lower odds of a positive medium-term headache outcome (odds ratio [OR] 0.43, 95% confidence interval [CI] 0.20–0.91). However, in the multivariate logistic regression model, headache exacerbation was no longer an independent predictor of treatment outcome (OR 0.65, 95% CI 0.28–1.51). Factors that independently predicted outcome were nausea (OR 0.12, 95% CI 0.02–1.00, p = 0.05), age (OR 1.68 for each decade increase in age, 95% CI 1.24–2.28), and medication overuse (OR 0.42, 95% CI 0.18–0.97). Conclusions: After controlling for nausea and other factors, headache exacerbation with DHE infusions is not an independent predictor of poor headache outcome and clinicians should not interpret its presence as a reason to stop treatment. The focus of management should be on controlling nausea as it is the most important modifiable factor in achieving a good headache outcome with an inpatient course of IV DHE for chronic migraine.